Simultaneous occurrence of quadruple lewis acid–base interactions between selenium atoms in selenocarbonyl dimers - Buralli, Gabriel Jesús (2017)
Fil: Buralli, Gabriel Jesús. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.